Isolasi, Seleksi, Karakterisasi Dan Identifikasi Bakteri Asam Laktat Penghasil Bakteriosin Dari Berbagai Buah Masak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Fruits are indicates as a habitat of lactic acid bacteria (LAB) because their chemical composition and micro environtment which needed to their life. The aim of this research was to study the diversity of lactic acid bacteria on some ripe fruits, to obtain lactic acid bacterial isolate which capable to produce bacteriocin, to know their phenothypic characteristic, classify an identify the isolates phenetically. Lactic acid bacteria were isolated from papaya, banana, pineapple and salak by using pour plate method and then purified by using streak plate method. All isolates were screened their potency to onhibit the growth of some pathogenic bacteria. The capacity to produce bacteriocin were determined by heating the cultural medium at 100Â°C up to 60 minutes and treating with the proteolytic enzyme (Proteinase K) at room temperature. The result of this experiment indicated that cultural medium from twelve isolates able to inhibit the growth of Staphylococcus aureus FNCC 0047. the best two of isolates (PE6 and PE9) also active to some pathogenic bacteria such as Eschericia coli FNCC 0091, Bacillus cereus FNCC 0057 and Salmonella tiphymurium FNCC 0050. the inhibitory compounds produce by the isolates...